Improving electrical, mechanical, thermal and hydrophobic properties of waterborne acrylic resin-glycidyl methacrylate (GMA) by adding multi-walled carbon nanotubes. (18th June 2020) - Wu, Mingyang; Ge, Shengsong; Jiao, Cuiyan; Yan, Zhangyin; Jiang, Heyun; Zhu, Yunfeng; Dong, Binbin; Dong, Mengyao; Guo, Zhanhu
Abstract: Multi-walled carbon nanotubes (MWCNTs)/waterborne acrylic resin nanocomposite coatings were synthesized by a solution mixing method using 3-aminopropyltriethoxysilane (KH-550) coupling agent as the curing agent. The improvements on thermostability, conductibility, mechanical performances, and hydrophobicity of the as-prepared composite coatings were evaluated. The conductivity was improved by six orders of magnitude compared to pure waterborne acrylic resin. CNTs greatly enhanced the thermostability and reduced the curing temperature. The tensile test showed that the introduction of CNTs significantly enhanced the mechanical performances of the resin. The sample with 5 wt% CNTs exhibited the largest tensile strength, which was higher than pure resin. Moreover, the coating had an improved surface hydrophobicity. 6 wt% CNTs increased the contact angle of the coating from 81.32° to about 90°. Graphical abstract: Image 1 Highlights: Carboxylated CNTs/waterborne acrylic resin modified with gycidyl methacrylate (GMA) was firstly prepared. 3-aminopropyltriethoxysilane (KH-550) was used not only as a coupling agent but also as a curing agent. The added CNTs significantly improved the electrical conductivity. The added CNTs significantly enhanced thermal stability and tensile strength of coating.